2021
DOI: 10.3390/cells10020309
|View full text |Cite
|
Sign up to set email alerts
|

Lung Mast Cells Have a High Constitutive Expression of Carboxypeptidase A3 mRNA That Is Independent from Granule-Stored CPA3

Abstract: The mast cell granule metalloprotease CPA3 is proposed to have important tissue homeostatic functions. However, the basal CPA3 mRNA and protein expression among mast cell populations has remained poorly investigated. Using a novel histology-based methodology that yields quantitative data on mRNA and protein expression at a single-cell level, the present study maps CPA3 mRNA and protein throughout the MCT and MCTC populations in healthy skin, gut and lung tissues. MCTC cells had both a higher frequency of CPA3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 47 publications
5
25
0
7
Order By: Relevance
“…At the same time, in our studies to identify specific MC proteases, we found that CPA3 can also be expressed in tryptase-positive human MCs with no chymase, including in the mucous membrane of the stomach and small intestine [48]. Similar data were obtained in a recent study showing different levels of CPA3 in MCs of the skin, lungs and intestines [10]. MCs with the expression of both specific proteases contained CPA3 in a greater amount than the MC phenotype "tryptase + chymase".…”
Section: Molecular Genetic Aspectssupporting
confidence: 89%
See 3 more Smart Citations
“…At the same time, in our studies to identify specific MC proteases, we found that CPA3 can also be expressed in tryptase-positive human MCs with no chymase, including in the mucous membrane of the stomach and small intestine [48]. Similar data were obtained in a recent study showing different levels of CPA3 in MCs of the skin, lungs and intestines [10]. MCs with the expression of both specific proteases contained CPA3 in a greater amount than the MC phenotype "tryptase + chymase".…”
Section: Molecular Genetic Aspectssupporting
confidence: 89%
“…MCs with the expression of both specific proteases contained CPA3 in a greater amount than the MC phenotype "tryptase + chymase". The presence of CPA3 in tryptase-positive MCs significantly complements the data on the functional significance of co-localization of CPA3 with chymase [7,10]. Moreover, in some pathological conditions, chymase-negative mast cells with CPA3 expression have been found [27,[49][50][51].…”
Section: Molecular Genetic Aspectssupporting
confidence: 75%
See 2 more Smart Citations
“…In contrast, in humans MMCs only express tryptase and are therefore named MC T , whereas CTMCs express both tryptase and chymase and are named MC TC . Notably, MC TC also express cathepsin G and both MC T and MC TC can express CPA3 at the mRNA level, but CPA3 protein is only found in MC TC [29,30].…”
Section: Introductionmentioning
confidence: 99%